Person and Value - Poli, Roberto (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
Preliminary to any adequate theory of the person is clarification of its ontological structure. For this purpose, it is useful to draw a distinction among at least three different ontological aspects of person, respectively corresponding to the dignity of life, to the acceptance or rejection of ethical values and the dignity corresponding to the qualities of an authentically human biography. It is reasonable to suppose that some of the traditional difficulties concerning the theory of the person depend on a failure to distinguish among these different ontological aspects. This paper presents some of the intricacies of the intermediate dimension of being a person, namely the idea of person as a subject with values, an entity that may, with greater or lesser ability, accede to values and accept or reject them intentionally.
Keywords: Person; value; emotion; Stein; Hartmann